Opsquare: A flat DCN architecture based on flow-controlled optical packet switches - Yan, Fulong; Miao, Wang; Raz, Oded; Calabretta, Nicola (Journal of optical communications and networking, 2017)
Aiming at solving the scaling issues of bandwidth and latency in current hierarchical data center network (DCN) architectures, we propose and investigate a novel optical flat DCN architecture in which the number of interconnected ToRs scales as the square of the optical packet switches’ (OPS) port count (OPSquare). The proposed flat DCN architecture consists of two parallel interand intra-cluster networks that are built on a single-hop OPS with nanosecond time and wavelength switching for efficient statistical multiplexing operations. Fast optical flow control is implemented for solving packet contentions that may occur at the buffer-less optical switches. The performance of OPSquare DCN in terms of scalability, packet loss, latency, and throughput is assessed by a numerical simulation employing OMNeT++ under realistic data center (DC) traffic. The results report a server-to-server latency of less than 2 /<spl mu>s (including packet retransmission), a packet loss <10 −5 at a load of 0.4, and aDC size of 10,240 servers with a ToR buffer size equal to 50 KB for all traffic patterns. Moreover, the cost and power consumption of the OPSquare DCN have been studied and compared with fat-tree DCN based on electrical switches and H-LION connected by an arrayed wave guide grating router (AWGR). The results indicate 23.8% and 39% cost and power savings, respectively, for the OPSquare DCN supporting 160,000 servers with respect to the fat-tree DCN. The OPSquare has a cost saving of 56% compared with H-LION for a 160,000-server DCN.